ACTION OF ETHYL EXTRACTS OF ANNONAMURICATA IN THE TRADITIONAL TREATMENT OF CERVICAL CANCER IN THE WISTAR RAT - MICHODJEHOUN, VIOUTOU LAETITIA; KOUKOUI SONON, AGOGBÉ SÈMAKO ISABELLE OMEDINE; HOUNDEFFO, TIBURCE ALIHONOU ADIHOU GNÉTOGON; HOUNSINOU, Sylvie; AIVODJI, Natacha; SEZAN, ALPHONSE; AHOKPE, ANGÈLE MÉLANIE (My University, 2017)
Our study focused on the action of ethyl extract of Annonamuricata in the traditional treatment of cervical cancer in the Wistarrat. This is an analytical, prospective and control study that took place at the Laboratory of Biomembranes and Cell Signaling of the University of AbomeyCalavi.The purpose of this study is to verify the effects of the ethyl extracts of the leaves of Annonamuricata on the differentiation of cervical cells in the Wistarrat. For this, an ethyl extraction was carried out using dried leaves powder of Annonamuricata and of ethanol at 90°, likewise the extraction of the leaves of Cycasrevoluta. The activity on differentiation was evaluated by assaying the total protein and alkaline phosphatase parameters on crushed cells of the Wistar rat uterus in which the differentiation of the cervical cells was induced beforehand by exposure to the powder and extracted Ethyls of Cycasrevoluta through a diet. Our sample included a sub-control population of 3 Wistar rats and one sub-population of 6 Wistars.PAL activity in the control sub-population is higher than in the sub-population-case. The PAL / total protein ratio of the sub-control population is significantly higher than in the sub-population case. These results make it possible to demonstrate the action of the extracts of Annonamuricata on the differentiation of the cells of the cervix of the rat.
Keywords: Annonamuricata; Cycasrevoluta; cervical cancer; extract; differentiation